WAYS TO INCREASE THE EFFECTIVENESS OF THE EDUCATIONAL PROCESS - Nazarov, Rustam (Журнал иностранных языков и лингвистики, 2023)
The article will provide a brief overview of the active teaching methods used in the work experience for the development of communicative speaking skills. Methods can be used in lessons in a non-linguistic institute, at different stages of the lesson.